2010
DOI: 10.1021/ie100230b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrolytic Carbon Composites Using Ethanol As Precursor

Abstract: Chemical vapor infiltration and deposition of carbon fiber bundles are applied to synthesize pyrolytic carbon composites using the oxygen-containing precursor ethanol. The influence of the temperature (1373 and 1423 K) and pressure (1−7 Pa) on the microstructure and the deposition rate of pyrolytic carbon are experimentally studied. Higher partial pressures of ethanol are demonstrated to favor the growth of highly ordered graphene-like pyrocarbon, whereas lower partial pressures help to suppress the carbon tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Models of CVI in porous carbons via multi-step CVI/CVD are based on the idea that complicated radical reactions in gas phase lead to the formation of small linear molecules C 2 eC 4 , aromatic benzene-like C 6 species and polycyclic aromatic (С 6 ) n hydrocarbons [21e23, 36,37] as well as to chemisorption of molecules/particles from gas phase onto the active sites of the matrix surface. During the synthesis of CCA750-41*, gas phase could exhibit an optimum ratio of aromatic to small linear hydrocarbons, which was necessary for the deposition of a high textured carbon layer according to Dong et al [36].…”
Section: Samplementioning
confidence: 99%
“…Models of CVI in porous carbons via multi-step CVI/CVD are based on the idea that complicated radical reactions in gas phase lead to the formation of small linear molecules C 2 eC 4 , aromatic benzene-like C 6 species and polycyclic aromatic (С 6 ) n hydrocarbons [21e23, 36,37] as well as to chemisorption of molecules/particles from gas phase onto the active sites of the matrix surface. During the synthesis of CCA750-41*, gas phase could exhibit an optimum ratio of aromatic to small linear hydrocarbons, which was necessary for the deposition of a high textured carbon layer according to Dong et al [36].…”
Section: Samplementioning
confidence: 99%
“…Apart from hydrocarbons, ethanol can be considered as an attractive alternative precursor for pyrolytic carbon formation. The presence of hydroxyl group in ethanol weakens the C-H bond, which may result in an increased reactivity in comparison with C 2 hydrocarbons [15]. The experimental studies of ethanol pyrolysis were reported in [16][17][18], and the major observed products were hydrogen, water, carbon monoxide, ethylene, methane, acetaldehyde, and formaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrolysis experiments in the presence of radical trappers (toluene) were performed in [18] in order to determine the rate constant of ethanol decomposition reaction into ethylene and water. The synthesis of pyrolytic carbon composites using ethanol as a precursor was reported in [15,21]. It was found that ethanol exhibits much higher deposition rate in comparison with methane.…”
Section: Introductionmentioning
confidence: 99%
“…Such products are often prepared by densification of a fibrous preform with a pyrolytic matrix of carbon through a chemical vapor infiltration or deposition process (CVI/CVD). This process consists in the deposition of a matrix of pyrocarbon on a substrate surface by thermal decomposition of gaseous hydrocarbons such as methane or propane [1][2][3][4][5], unsaturated species (ethylene, acetylene…) [6][7] or organic species [8] at high temperature and low pressure. The CVD/CVI of pyrocarbon from pyrolysis of a hydrocarbon precursor is a complex phenomenon which is still an object of scientific research despite it has been widely studied for several decades.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, during the last few years, a significant number of experimental and modeling studies has been carried out in order to elucidate the chemistry of pyrocarbon deposition and to establish the most important parameters involved in the formation of pyrocarbon, as temperature, pressure, residence time or the ratio of the carbon fibers area and the volume of the gas phase (A/V) [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%